Fatigue during maximal sprint cycling: Unique role of cumulative contraction cycles - Tomas, A.; Ross, E. Z.; Martin, J. C. (Medicine & Science in Sports & Exercise, 2010)
Abstract: Maximal cycling power has been reported to decrease more rapidly when performed with increased pedaling rates. Increasing pedaling rate imposes two constraints on the neuromuscular system: 1) decreased time for muscle excitation and relaxation and 2) increased muscle shortening velocity. Using two crank lengths allows the effects of time and shortening velocity to be evaluated separately.